A sports oriented concept for developing multimedia learning and teaching materials - Baca, A.; Eder, C.; Strubreither, O. (International Journal of Computer Science in Sport, 2005)
In the years 2001-2003 an internet-based information system was developed to assist students in learning and comprehending theoretical basics and concepts of sport scientific disciplines (biomechanics, physiology, psychology, etc.). In contrast to many other multimedia systems used as eLearning tools in sport science, the starting points are sports and not disciplines. Questions related to these sports are asked and then answered from the perspective of sport scientific disciplines in a highly interdisciplinary way. Not least because of positive experiences with students, who participated in the project, the development of multimedia learning and teaching materials has been integrated into the education program. As part of their diplom a works, students are encouraged to create multimedia software. Again, the systems to be developed focus on sports, what appears to have a high motivational effect on the students. Throughout the last years very impressive packages have been developed. As a consequence of this process, the amount of multimedia modules and submodules for different sports is continuously growing. A standardized, structured framework is therefore under development. Modules and submodules are organized in the form of a matrix of sports and sport scientific disciplines. The overall system is based on an open source based content management system simplifying the integration of all information assets.